Design and application of a low soot emission targeted combustion chamber for diesel engines - Karaca, Caner (My University, 2021)
Diesel engine emission levels are strictly regulated over the year. Meeting these emission regulations has always been a challenging job for diesel engine developers. Considering the cost problems and complexities of diesel engine aftertreatment systems, in order to meet the soot and NOx levels, engineers had to come up with alternative design solutions. Since changing the combustion chamber design has always been a more cost effective and easily applicable solution compared to complex diesel engine aftertreatment devies, various chamber designs have been researched and tested by engineers. The geometrical shape of the combustion chamber is particularly significant in order to improve the turbulent flow structures and in-cylinder flow velocities that would affect combustion efficiency and engine-out emissions. Two of the most widely used designs are mexican hat and stepped-lip chambers. The stepped lip design in particular, has been widely investigated due to their fuction of promoting recirculating flow structures which enhances fuel-air mixing and resulting with lower soot emission levels. The main objective of this thesis is to investigate the effect of stepped-lip combustion chamber design and compare the in-cylinder vortex structures with a conventional mexican hat chamber. A 3D CFD model has been carried out in order to understand the in-cylinder flow structures and vortex formations. Then an experimental study has been conducted with a single cylinder diesel engine with an in-line pump injection system and soot emission levels of both mexican hat and stepped lip combustion chambers have been compared.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Diesel engine; Combustion chamber; Stepped lip; CFD analysis; Soot emission